Role of jeotgal, a Korean traditional fermented fish sauce, in microbial dynamics and metabolite profiles during kimchi fermentation. (1st November 2018) - Jung, Min Young; Kim, Tae-Woon; Lee, Changsu; Kim, Joon Yong; Song, Hye Seon; Kim, Yeon Bee; Ahn, Seung Woo; Kim, Ju Seok; Roh, Seong Woon; Lee, Se Hee
Highlights: Effects of jeotgal on kimchi lactic acid bacteria succession and metabolite changes. Jeotgal was facilitating the reduction of coliform originated from raw materials. Jeotgal affected the growth of LAB, which produce GABA, lactate, acetate, and mannitol. Abstract: We investigated the effects of jeotgal (fermented fish sauce) on kimchi fermentation, with or without saeu-jeot and myeolchi-jeot. Bacterial community analysis showed that Leuconostoc, Weissella, Lactobacillus, and Tetragenococcus were the dominant genera; however, their succession depended on the presence of jeotgal. Leuconostoc gasicomitatum was the dominant species in kimchi without jeotgal, whereas Weissella koreensis and Lactobacillus sakei were the dominant species in kimchi with myeolchi-jeot and saeu-jeot, respectively. Metabolite analysis, using 1 H NMR, showed that the amounts of amino acids and gamma-aminobutyric acid (GABA) were higher in kimchi with jeotgal. Increases in acetate, lactate, and mannitol contents depended on fructose consumption and were more rapid in kimchi with jeotgal. Moreover, the consumption of various amino acids affected the increase in kimchi LAB. Thus, the role of jeotgal in kimchi fermentation was related to enhancement of taste, the amino acid source, and the increases in levels of functional metabolites.